Trends in Methamphetamine Use in the Mainland of China, 2006–2015 - Zhang, Bo; Yan, Xiangyu; Li, Yongjie; Zhu, He; Lu, Zuhong; Jia, Zhongwei (Frontiers in Public Health, 2022)
Background: Methamphetamine is the most prevalent drug in the mainland of China, yet few studies on the nonmedical use of methamphetamine nationwide have been conducted. This study aimed to examine the trends in the prevalence of nonmedical methamphetamine use and to explore the flow pattern of internal migrant methamphetamine users in the mainland of China. Methods: Data were extracted from the National Dynamic Management and Control Database for Drug Users (NDMCD). Joinpoint regressions were used to examine trends in the prevalence and population size of methamphetamine use. Results: A total of 1,821,468 methamphetamine use cases registered in NDMCD from 2006 to 2015 were identified. The number of methamphetamine use cases presented an increasing trend in all age subgroups, and among them, the elderly increased the fastest (annual percent change [APC2006-2015], 122.9; 95% CI, 113.0 133.3; p<0.001). The prevalence of methamphetamine use increased from 4.69 per 100,000 population in 2008 to 45.38 per 100,000 population in 2015 (APC2008-2015, 36.1; 95% CI, 31.9 40.6; p<0.001). The regions of the Pearl River Delta, Yangtze River Delta, and Beijing-Tianjin-Hebei Urban Agglomeration absorbed over 96% of all internal migrant methamphetamine use cases, and the number of migrant methamphetamine use cases presented increased trends in these three regions. Conclusions: The increasing trends in methamphetamine use have become a threat to all age groups in China. Substance use prevention programs should focus on internal migrant drug users, especially in economically developed regions.